2014
DOI: 10.1021/es503681p
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization Time-of-Flight Mass Spectrum Analysis Method of Polyaluminum Chloride Flocculants

Abstract: Electrospray mass spectrometry has been reported as a novel technique for Al species identification, but to date, the working mechanism is not clear and no unanimous method exists for spectrum analysis of traditional Al salt flocculants, let alone for analysis of polyaluminum chloride (PAC) flocculants. Therefore, this paper introduces a novel theoretical calculation method to identify Al species from a mass spectrum, based on deducing changes in m/z (mass-to-charge ratio) and molecular formulas of oligomers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
(168 reference statements)
0
25
0
Order By: Relevance
“…Feng et al had improved the method for identification of Al species in ESI-MS spectrum [25,26]. The general formula for identification of Al species form was…”
Section: Speciation Characterization Through Esi-msmentioning
confidence: 99%
“…Feng et al had improved the method for identification of Al species in ESI-MS spectrum [25,26]. The general formula for identification of Al species form was…”
Section: Speciation Characterization Through Esi-msmentioning
confidence: 99%
“…Chen et al reported that Al 13 showed high positive charge, stable structure, and strong binding affinity, and is the most active Al species in Al salts responsible for coagulation process [25]. In addition, Al 13 also contributed most to the amount of Al species for PACl in basicity range from 1.5 to 2.5 [26,27]. Our previous study indicated that pH significantly affected the Al species distribution of AlCl 3 and preformed PACl, and in acidic or alkaline pH region the ratios of monomeric Al increased whereas polymeric and colloidal Al species decreased as compared to the near-neutral pH region [21].…”
Section: Removal Efficiency Of Fluoride By Different Al Coagulantsmentioning
confidence: 99%
“…In this case fluoride removal was mainly attributed to physical adsorption and ion exchange effects [4,31], and the weakly acidic and acidic pH favored its removal. In B ranges from 1.0 to 1.5, PACl includes different Al species such as Al 2 , Al 4 , Al 7 and Al 13 et al [27], the ratios of monomeric Al species were observed to increase with lowered B. In this case coagulation dominated in the removal of fluoride, and different mechanisms such as complexed precipitation, charge attraction, and ion exchanges involve in and facilitated fluoride removal accordingly [32,33].…”
Section: Removal Efficiency Of Fluoride By Pacl With Different Basicitymentioning
confidence: 99%
“…The percent concentration of each species was determined by the ratio of the peak intensity for each species to the total intensity of all of the species (Feng et al, 2015. The samples were injected into the spectrometer at a flow rate of 10 L min In this study, ultra pure water was used as the black sample, and the mass spectra of black sample is shown in S- Fig.…”
Section: Electrospray Ionization Time-of-flight Mass Spectrometrymentioning
confidence: 99%
“…Recently, ESI-TOF-MS has been applied in metal ions species identification for determination of molecular mass (Feng et al, 2015;Feng et al, 2011;Bi et al, 2012). In this study, two coagulants at the same concentration of 0.2 mM were used to detect the Al species distributions.…”
Section: Variation Of Floc Characteristics and Filterability With Ph mentioning
confidence: 99%